Partnership as experimentation: Business organization and survival in Egypt, 1910-1949 - Cihan Artunç; Timothy Guinnane (Yale University, Economic Growth Center, 2017)
The relationship between legal forms of firm organization and economic development remains poorly understood. Recent research disputes the view that the joint-stock corporation played a crucial role in historical economic development, but retains the view that the costless firm dissolution implicit in non-corporate forms is detrimental to investment. We demonstrate the benefits of costless dissolution in an environment where potential business partners are not fully-informed. Using a multi-armed bandit model, we show that an experimentation mechanism creates a spike in dissolution rates early in firms' lives, as less productive matches break down and agents look for better matches. We test the model's predictions using a novel firm-level dataset comprising more than 12,000 enterprises established in Egypt between 1910 and 1949. Most partnerships dissolved within two years; afterwards, the risk of dissolution dropped to a lower, steady level. Corporations had much more uniform and lower attrition rates. Companies made up of partners who had been in business before also had flatter dissolution rates, confirming the link between learning and the early break-up of partnerships. The partnership reflected a trade-off between committing to a partner and sorting into potentially better matches.
Keywords: 330